EMPLOYING FINANCIAL ACCOUNTING STANDARDS FOR ENTITIES WITHOUT PUBLIC ACCOUNTABILITY FOR AUDITING - Rusaktiva, Akie; Nugraha, Adri Putra (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2012)
Financial Accounting Standards for Entities Without Public Accountability (FAS-EWPA) is a financial accounting standards issued by The Indonesian Institute of Accountants or Ikatan Akuntan Indonesia (IAI) and endorsed by the Financial Accounting Standards Board of Indonesian Accountants or Dewan Standar Akuntansi Keuangan Ikatan Akuntan Indonesia (DSAK IAI) and intended for small and medium enterprises. The underlying priciple of IAI in issuing this particular standards is the attempt to facilitate small and medium enterprises in arranging their financial reports. If this standard is not issued, they have to follow the new FAS (which is stage of adopting IFRS – full convergence 2012) to arrange their financial reports. The application of this FAS-EWPA based IFRS is relatively more complex and expensive for small and medium enterprises. FAS-EWPA adopted some parts of IFRS (International Financial Reporting Standards) for small-medium enterprises (IFRS for Small-Medium-sized Entities/SMEs). This study aims to describe the layout of the difference measurement, assessment, report and the implementation of auditing standards between FAS-IFRS and FAS-EWPA. This study employed descriptive qualitative technique of data analysis by reviewing literature and analysing the field concerning with the implementation of Financial Accounting Standards Statements (FASS) and FAS-EWPA. Specifically, the secondary data of this study are FAS-IFRS and FAS-EWPA. The findings shows that there is a difference presentation and disclosure of financial statements between entities which report using FAS-IFRS and FAS-EWPA. Therefore the perceived program and audit procedures will be different because it will be tailored to the presentation and objectives the audit, suppose that in the implementation of FASS and EWPA, there is a difference in the assertions about the disclosure/presentation. For other assertions about existence, completeness, rights and obligations as well as assessment and allocation, basically, between FASS and EWPA, they have a common concept. While in presentation assertions as has been described earlier, the FAS-EWPA has a simpler form than with FASS, therefore there is a definitely difference in terms of the presentation between the two.